Kekerasan Ilahi dalam Yosua 6:1-27: Tinjauan Historis-Kritis atas Pembinasaan Yerikho - Jehosua Geovalentcia Lansart; Asniathy Asseng; Silfayani Banni; Meylin Imba (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Texts depicting violence in the Old Testament, particularly Joshua 6:1–27, are often cited as evidence that the Bible legitimizes divine violence and genocide. This study aims to analyze the narrative of the conquest of Jericho through a historical-critical approach by integrating narrative structure analysis, historical-religious context, and a conceptual study of herem. The method used is a literature review with a qualitative approach that situates the text within the context of the Ancient Near East. The results of the study indicate that Joshua 6 is a systematically constructed theological narrative intended to affirm YHWH’s sovereignty as the Warrior-God and His faithfulness to the covenant with Israel. The concept of herem does not merely signify annihilation but functions as a mechanism for the sanctification of the people and the affirmation of covenantal identity in the face of the threat of syncretism. Furthermore, the use of war language in this text reflects the hyperbolic rhetoric characteristic of ancient literature, and thus cannot be read literally as a legitimization of modern violence. Consequently, a historical-critical reading affirms that this narrative is not a justification for genocide, but rather a theological construction that serves to shape the identity of faith and the understanding of God’s holiness and sovereignty in the history of Israel.